Fine Spatial Scale, Frequent Morphological Monitoring of Urbanised Beaches to Improve Coastal Management (2021)
ABSTRACT: Between 1959 and 2010, a coastline retreat of 2.4 m/year and erosion of up to 174 m were recorded around Turbo, in northern Colombia. This degraded coastal system is the result of a poorly planned coastal defence scheme, combined with a lack of formal technical methodologies for diagnosis and monitoring. The coastal system cannot provide the protection services required by the local community. From 2017 to 2019, the group monitored urban beach profiles in a small area close to the town of Turbo, in the wet and the dry seasons, as part of a coastline analysis to identify morphodynamic trends in the area. The results show a net shoreline accretion of up to 30 m and positive sedimentary accumulation of up to 45.8 m3/m. To the north of the study area, sediment accumulation is evident at the Turbo River Delta. The 34 coastal protection structures in the study area have a high k index (~0.7), suggesting that they are the main drivers controlling the trend of sediment accumulation. The correlation of geomorphological, oceanographic, and anthropic variables related to the presence of coastal structures, is necessary in order to set up efficient coastal protection schemes.